Silicon supplementation enhances productivity, water use efficiency and salinity tolerance in maize - Alayafi, Abdullah H.; Al-Solaimani, Samir G. M.; Abd El-Wahed, Mohamed H.; Alghabari, Fahad M.; Sabagh, Ayman El (Frontiers in Plant Science, 2022)
Silicon (Si) supplementation is an ecofriendly approach to alleviate abiotic stresses globally. Therefore, a field experiment was conducted in two successive growth seasons (2019-20) to investigate the effect of foliar application of Si at two concentrations (1 and 2 kg ha-1) on the growth and yield of three maize cultivars (ES81, ES83, and ES90) under three levels of irrigation salinity) [1000 (WS1), 2000 (WS2) and 3000 (WS3) mg L-1). In this study, we used a trickle irrigation system during experiments. At harvesting stages, different physiological parameters such as growth, yield, and salinity tolerance were studied. Si application significantly mitigated the harsh effects of salinity on growth and yield components of maize, which increased at all concentrations of Si. In irrigation with S3 salinity treatment, grain yield was decreased by 32.53%, however, this reduction was alleviated (36.19%) with the exogenous application of Si at 2 kg ha-1. At salinity levels, Si application differentially increased maize grain yield (t ha-1) to its maximum level under WS of 1000 mg L-1, and its minimum level under WS of 3000 mg L-1. Accordingly , the highest grain yield increased under Si application of 2 kg ha-1, regardless of salinity level and the cultivar ES81 achieved the highest level of tolerance against water salinity treatments.